Determination of magnetic anisotropy in the LnTRENSAL complexes (Ln = Tb, Dy, Er) by torque magnetometry - Perfetti, Mauro; Lucaccini, Eva; Sorace, Lorenzo; Costes, Jean Pierre; Sessoli, Roberta (Inorganic chemistry, 2015)
We report here a study about the magnetic anisotropy of the LnTRENSAL complexes (Ln = Tb, Dy, Er) performed by using cantilever torque magnetometry and electron paramagnetic resonance. For all of the compounds, we extracted a set of crystal-field parameters to obtain the energy-level splitting of the ground-state multiplet.